Identification of differentially expressed circular RNAs in human colorectal cancer - Peili Zhang; Zhigui Zuo; Wenjing Shang; Aihua Wu; Ruichun Bi; Jianbo Wu; Shaotang Li; Xuecheng Sun; Lei Jiang (Tumor Biology)
Circular RNA, a class of non-coding RNA, is a new group of RNAs and is related to tumorigenesis. Circular RNAs are suggested to be ideal candidate biomarkers with potential diagnostic and therapeutic implications. However, little is known about their expression in human colorectal cancer. In our study, differentially expressed circular RNAs were detected using circular RNA array in paired tumor and adjacent non-tumorous tissues from six colorectal cancer patients. Expression levels of selected circular RNAs (hsa_circRNA_103809 and hsa_circRNA_104700) were measured by real-time polymerase chain reaction in 170 paired colorectal cancer samples for validation. Statistical analyses were conducted to investigate the association between hsa_circRNA_103809 and hsa_circRNA_104700 expression levels and respective patient clinicopathological features. Receiver operating characteristic curve was constructed to evaluate the diagnostic values. Our results indicated that there were 125 downregulated and 76 upregulated circular RNAs in colorectal cancer tissues compared with normal tissues. We also first demonstrated that the expression levels of hsa_circRNA_103809 ( p  < 0.0001) and hsa_circRNA_104700 ( p  = 0.0003) were significantly lower in colorectal cancer than in normal tissues. The expression level of hsa_circRNA_103809 was significantly correlated with lymph node metastasis ( p  = 0.021) and tumor-node-metastasis stage ( p  = 0.011), and the expression level of hsa_circRNA_104700 was significantly correlated with distal metastasis ( p  = 0.036). The area under receiver operating characteristic curves of hsa_circRNA_103809 and hsa_circRNA_104700 were 0.699 ( p  < 0.0001) and 0.616 ( p  < 0.0001), respectively. In conclusion, these results suggest that hsa_circRNA_103809 and hsa_circRNA_104700 may be potentially involved in the development of colorectal cancer and serve as potential biomarkers for the diagnosis of colorectal cancer.